Characterization of Inflammatory Bowel Disease in Hospitalized Elderly Patients in a Large Central Canadian Health Region - Peter Stepaniuk; Charles N Bernstein; Zoann Nugent; Harminder Singh (Canadian Journal of Gastroenterology and Hepatology)
OBJECTIVE: To determine differences in phenotype and treatment among hospitalized elderly and young patients with inflammatory bowel disease (IBD), and the utility of International Classification of Diseases, 10th Revision (ICD)-10 codes in hospital discharge abstracts in diagnosing IBD in elderly patients.